Double‐hydrophilic polyether antiscalant used as a crystal growth modifier of calcium scales in cooling‐water systems. Issue 2 (20th August 2013) - Liu, Yahui; Zhou, Yuming; Yao, Qingzhao; Huang, Jingyi; Liu, Guangqing; Wang, Huchuan; Cao, Ke; Chen, Yiyi; Bu, Yunyun; Wu, Wendao; Sun, Wei
ABSTRACT In this study, we synthesized a novel double‐hydrophilic poly(ethylene glycol) (PEG)‐based crystal growth modifier polyethylene glycol double‐ester of maleic anhydride/ acrylic acid named PEGDMA/AA, whose structure was still linear but also had some differences from a traditional chelating linear polymer, in which the PEG segment was incorporated. The scale inhibition behavior of PEGDMA/AA was evaluated by means of a static scale inhibition method. As the polymerization degree of PEGnDMA was 8 (n = 8), the maximum inhibitory toward calcium carbonate (CaCO3) and calcium sulfate (CaSO4) were 89.0 and 98.8% at dosage levels of 12 and 3 mg/L, respectively. Comparisons with other inhibitors were also carried out. Characterization of the CaCO3 and CaSO4 scales with scanning electron microscopy and transmission electron microscopy proved that great changes in the size and morphology of the calcium scales took place under the influence of PEG8DMA/AA. X‐ray diffraction and diffraction patterns further confirmed the impact of PEG8DMA/AA as a crystal growth modifier. The three supposed mechanisms, (1) chelating solubilization, (2) multilayer type of adsorption, and (3) electrostatic repulsion function, are also described in detail. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 39792.